1981
DOI: 10.1111/j.1748-1716.1981.tb06700.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucagon, dibutyrylic cyclic AMP and insulin on bile production in the intact rat and the perfused rat liver

Abstract: The effect of glucagon, dibutyrylic cyclic AMP (DBcAMP) and insulin on bile flow and composition was studied in fasting. Nembutal anesthetized intact rats and perfused rat livers. In intact rats the infusion of glucagon (0.5 microgram x kg b.w.-1 x min-1) resulted in a parallel increase in bile flow and 14C-erythritol clearance of approx. 20%. The biliary excretion rate of electrolytes increased, whereas the net ductular fluid transport and the excretion rate of bile acids remained unchanged. Thus glucagon cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Glucagon increased the rate of CP-/HCO exchange by 100% when meastred during Cl -removal or by 50% after Cl -readmission. In comparison, the excretion rates of bicarbonate in bile were increased by 34% in the rat (4) and by 71% in the guinea pig (2). A number of studies have shown previously that glucagon, after stimulation of adenylate cyclase activity, increased the intracellular level of cAMP in isolated rat hepatocytes (31), in the isolated perfused rat (39), and in guinea pig liver (2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Glucagon increased the rate of CP-/HCO exchange by 100% when meastred during Cl -removal or by 50% after Cl -readmission. In comparison, the excretion rates of bicarbonate in bile were increased by 34% in the rat (4) and by 71% in the guinea pig (2). A number of studies have shown previously that glucagon, after stimulation of adenylate cyclase activity, increased the intracellular level of cAMP in isolated rat hepatocytes (31), in the isolated perfused rat (39), and in guinea pig liver (2).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, glucagon, at physiological doses, induces a bicarbonate-rich choleresis in humans (1) as well as in many different animal species, including the guinea pig (2), dog (3), and rat (4). Mechanisms of glucagon choleresis are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…31 In the liver, insulin increases bile flow in several species. [13][14][15][16]32,33 The choleretic effect of insulin is direct and not mediated by changes in the plasma levels of hormones (e.g., glucagon and somatostatin) or glucose. 15,32,34 Although the mechanism of insulin choleresis is undefined, studies showed that (1) insulin acts at the bile canaliculus since insulin-induced choleresis is associated with increased erythritol clearance 16 and (2) insulin increases the bile salt-independent fraction of bile flow but it does not alter bile salt secretion.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,8 Insulin stimulates canalicular bile secretion in dogs, rats, and guinea pigs. [13][14][15] The concept that insulin stimulates canalicular bile flow by interaction with hepatocytes is supported by studies in dogs showing that insulin increases erythritol clearance. 16 No information exists regarding (1) the functional expression of insulin receptors in cholangiocytes and (2) the role and mechanism of action of insulin in the regulation of ductal secretion.…”
mentioning
confidence: 99%
“…9-11) was made in the early 1980s from the Institute of Physiology at Aarhus University (71)(72)(73)(74)(75)(76). The main purpose of the study was to examine the mechanism and regulation of bile acid-independent canalicular bile production.…”
Section: Mechanism and Regulation Of Hepatic Bile Productionmentioning
confidence: 99%